2017
DOI: 10.1086/690907
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Assembly of Communities in Butterfly Mimicry Rings

Abstract: Species co-occurrence in ecological communities is thought to be influenced by multiple ecological and evolutionary processes, especially colonization and competition. However, effects of other interspecific interactions and evolutionary relationships are less explored. We examined evolutionary histories of community members and roles of mutualistic and parasitic interactions (Müllerian and Batesian mimicry, respectively) in the assembly of mimetic butterfly communities called mimicry rings in tropical forests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 87 publications
0
33
0
Order By: Relevance
“…Both the color and the band of this butterfly may help it form a mimicry ring with other local species that share similar traits (Joshi, Prakash, & Kunte, ; Mallet & Gilbert, ). Other species of palatable Papilio butterflies are known Batesian mimics of unpalatable, aposematic butterflies (Chai, ; Kunte, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both the color and the band of this butterfly may help it form a mimicry ring with other local species that share similar traits (Joshi, Prakash, & Kunte, ; Mallet & Gilbert, ). Other species of palatable Papilio butterflies are known Batesian mimics of unpalatable, aposematic butterflies (Chai, ; Kunte, ).…”
Section: Discussionmentioning
confidence: 99%
“…While the color phenotypes of lineages at different lifestages were determined by the lifestage vulnerability and the visual and phytochemical backgrounds of lifestages, the broad evolutionary pattern may be influenced by several macroecological factors such as the latitudinal diversity gradient, environmental filters, and community dynamics that are known to influence the evolution of functional traits, such as color defenses (Elias & Joron, ; Joshi, Prakash, & Kunte, ; Kraft, Cornwell, Webb, & Ackerly, ; Losos, ). The widespread incidence of aposematism and crypsis across tropical and temperate lineages experiencing distinct environments indicates a limited role of phylogenetic constraint, geography, and macroevolutionary processes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if habitats are more homogeneous, selection imposed by habitat may favor similar warning signals, leading to similar color patterns. In fact, the formation of multiple mimetic rings is more common in heterogeneous tropical than in homogeneous temperate zones (Sheppard et al, 1985;Beccaloni, 1997;Joshi et al, 2017). Second, our analyses showed that selective pressure exerted by the cooccurrence of other unpalatable species is enough for the emergence of distinct mimetic rings in a community, if the unpalatable species are specialized in the same habitat.…”
Section: Discussionmentioning
confidence: 72%
“…We already know that palatable mimics, i.e. Batesian mimics, rapidly converge towards the color trait pattern of species they co-occur (Joshi et al, 2017) and also influence the evolution of the mimetic rings (Franks & Noble, 2004). Therefore, we suggest that future works should investigate what are the effects of including Batesian mimics in a heterogeneous community for the formation of mimicry rings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation